2019
DOI: 10.3390/cells8121561
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Stiffness Modulates Renal Progenitor Cell Properties via a ROCK-Mediated Mechanotransduction Mechanism

Abstract: Stem cell (SC)-based tissue engineering and regenerative medicine (RM) approaches may provide alternative therapeutic strategies for the rising number of patients suffering from chronic kidney disease. Embryonic SCs and inducible pluripotent SCs are the most frequently used cell types, but autologous patient-derived renal SCs, such as human CD133+CD24+ renal progenitor cells (RPCs), represent a preferable option. RPCs are of interest also for the RM approaches based on the pharmacological encouragement of in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…This impact has been demonstrated with other proteins and polymers [34,46]. An increase in Young's modulus have been linked to positive effects such as cell proliferation and spreading, but also negative responses in particular apoptosis [47,48]. This fundamental also applies to decreased stiffness where studies have shown that there can be a positive influence such as increased focal adhesion properties and also some negatives with decreased cell motility [49,50].…”
Section: Discussionmentioning
confidence: 89%
“…This impact has been demonstrated with other proteins and polymers [34,46]. An increase in Young's modulus have been linked to positive effects such as cell proliferation and spreading, but also negative responses in particular apoptosis [47,48]. This fundamental also applies to decreased stiffness where studies have shown that there can be a positive influence such as increased focal adhesion properties and also some negatives with decreased cell motility [49,50].…”
Section: Discussionmentioning
confidence: 89%
“…The absence of APOL1 also promotes parietal epithelial cell quiescence; the microRNA miR-193a suppresses APOL1 translation 59 . Under conditions of mechanical stress 60 , impaired APOL1-miR-193a axis (for example, in those with the G1 or G2 genotype) 59 or persistent NOTCH expression 61 , activated parietal epithelial cells cannot properly differentiate into podocytes and contribute to the formation of hyperplastic lesions and fibrous lesions, including FSGS 58,62 , by synthesizing and releasing extracellular matrix 63 (FiG. 4).…”
Section: Oncotic Pressurementioning
confidence: 99%
“…However, it was rapidly recognized that substratum stiffness strongly influenced the outcome of cell receptor interaction with bound ligands [ 15 , 16 ]. Thus, when renal cells were deposited on collagen-coated hydrogels with an elastic modulus 2 ranging between 0.2 kPa and 50 kPa, cell proliferation rate increased proportionally to the substrate stiffness [ 17 ]. However, tendon-derived stem cells deposited on gelatin hydrogels with a stiffness ranging between about 2 kPa and 25 kPa displayed more active growth on softer surfaces [ 18 ].…”
Section: Cell Behaviour Is Strongly Influenced By Mechanical Parametersmentioning
confidence: 99%